Collibacillosis in newborn yak calves and antibiogram profile of rectal flora isolated from the same - BANDYOPADHYAY, SAMIRAN; SASMAL, DEVASIS; GHOSH, MONOJ K; BORAH, BINOD D; BORA, MONJIT; BISWAS, TAPAS K (The Indian Journal of Animal Sciences, 2011)
Rectal swab samples from the diarrhoeic yak calves yielded mostly E. coli, Sabnonella spp, Enterobactor spp, Staphylococclls spp, Streptococci spp. and Pseudonlonas aeruginosa. Of the 35 strains of E. coli recovered, 26 were typed into 9 different sero-groups, viz. 05, 011, 012, 015, 088, 096, 0146, 0166, 0172. The antibiogram results revealed highest sensitivity to norfloxacin, cefotaxitne, gentamicin followed by ciprofloxacin, tetracycline and chloramphenicol. Haenlatological examination revealed a slight reduction of haemoglobin level and rise ofPCV in all the calves. However, leucocytosis was evident with marked neutrophilia in all the calves indicating acute bacterial infection.Â